Coregistration of brain single-positron emission computed tomography and magnetic resonance images using anatomical features - de Oliveira, Lucas Ferrari (Springer-Verlag, 2000)
The present report describes a computer tool for the coregistration of single-positron emission computed tomography (SPECT) and magnetic resonance (MR) images to aid the diagnosis. Two types of images are used for some neurologic diseases: one of them anatomic (magnetic resonance) and the other metabolic (SPECT), with the specialist being required to make a mental integration of the examinations. This procedure can be improved by using a computer tool that might permit the presentation of this information in a single image. The coregistration is performed on the basis of pairs of points positioned by a specialist according to the structures present in the images and the least squares error is calculated between them using Euclidean distance. Coinciding planes and section thickness are selected for the two modalities and the SPECT image is processed so as to have the same spatial resolution as the resonance image.